2009
DOI: 10.1007/978-1-60761-198-1_28
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Imaging Techniques to Visualize Chemotactic Signaling Events on the Membrane of Living Dictyostelium Cells

Abstract: In this chapter, we describe methods to monitor signaling events at the single-molecule level on the membrane of living cells by using total internal reflection fluorescence microscopy (TIRFM). The techniques provide a powerful tool for elucidating the stochastic properties of signaling molecules involved in chemotaxis of the cellular slime mold Dictyostelium discoideum. Taking cAMP receptor 1 (cAR1) as an example of a target protein for single-molecule imaging, we describe the experimental setup of TIRFM, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…In Fig. 2B, the number of molecules that remained bound to the membrane was counted every 33 msec beginning from the onset of membrane association, normalized by the total number of molecules and plotted against time [23], [24]. The decay rate of the number of molecules on the membrane, which corresponds to the membrane dissociation rate, varied depending on the number of mutations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 2B, the number of molecules that remained bound to the membrane was counted every 33 msec beginning from the onset of membrane association, normalized by the total number of molecules and plotted against time [23], [24]. The decay rate of the number of molecules on the membrane, which corresponds to the membrane dissociation rate, varied depending on the number of mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Single molecules of wild type PTEN-Halo and PTEN i -Halo were visualized through objective type TIRFM. Details of the TIRFM configuration are described elsewhere [23].…”
Section: Methodsmentioning
confidence: 99%
“…Single-particle tracking (SPT) methods have been used to study the mobility of GPCR fusion proteins of with fluorescent proteins [63, 64], enzyme tags (HaloTag or ACP tag) that allow specific conjugation with fluorophores [65, 66], or epitope tags that allow visualization with gold-tagged Fab antibody fragments [63]. SPT has been used to infer receptor binding of fluorescent protein fusion constructs of heterotrimeric G proteins [67, 68].…”
Section: Escaping the Flatlands One Molecule At A Time: Concluding Rementioning
confidence: 99%
“…Optical microscopic methods, such as fluorescent video imaging, show molecular dynamics in single living cells. 3,4 The optical microscopic technique has been applied to imaging of bacterial cells and provides insights about molecular dynamics in vivo. For example, Kim et al observed the dynamics of the single cytoskeletal protein MreB in living bacterial cells using a total internal reflection fluorescence microscope.…”
Section: Introductionmentioning
confidence: 99%